STUDI DESKRIPTIF KONSEP PEMAHAMAN DIRI NEGATIF SISWA KELAS VII D DI MTs NEGERI 3 CIREBON - Doefi, Martina; saepulloh, aep; Susandi, Ardi Dwi (Jurnal Eksplorasi Bimbingan dan Konseling, 2025)
The concept of self-understanding of class VII D students is still negative, in principle, class VII D students are individuals in school and need to be given guidance in the form of self-development which is individual service or group service. In accordance with the developmental age and the level of transition from childhood to early adolescence, it is known as the transitional period or transitional period. This research is motivated by the negative self-understanding attitude of students of class VII D, the importance of the appearance of adult modeling as a process of imitation that students will understand to form a positive self-understanding. The purpose of this study was to describe the concept of negative self-understanding of class VII D students at MTs Negeri 3 Cirebon. This type of research is a descriptive qualitative research with primary data sources for class VII D students according to the negative self-understanding concept indicators, together with 5 respondents (YM, AL, CH, AN, FR) and secondary data including class VII counseling teachers, Homeroom class VII D. The instruments used in this study were interview guides, observation guidelines, documentation guidelines. The analysis used was data triangulation technique. The results of the research that has been carried out are negative self-understanding concepts.It is known that students who have a self-concept with negative indicators are 5 out of 32 students of class VII D at MTs Negeri 3 Cirebon. Negeri 3 Cirebon in the academic year 2020/2021 tends to a negative self-understanding concept.